Broke at the buffet: food insecurity in America - Hawley, Charles William (Kansas State University, 2009)
It is the intention of this thesis to come to a better understanding of the factors that lead to food insecurity, a concept for understanding if people have enough food to eat. The tool for household measurement was developed by the United States Department of Agriculture, and is the backbone of the Food Security Supplement, which is conducted annually as part of the Current Population Survey. Three literature are reviewed: concentration of markets, civic agriculture and localism, and food security and nutrition. Each approaches understanding food security from a different angle offering insights along with its shortcomings. Most US studies consider food insecurity as a contributing component of poor health. In this study, I ask instead, "What are the major predictors of household food insecurity?" Using data from the Food Security Supplement of the Current Population Survey from 2000 to 2007, I use descriptive statistics and logistic regression to investigate the causes of food insecurity. I show that as currently measured food insecurity is largely a function of economic inequalities. Within this broad finding, however, I also show that households in a principal city and nonmetropolitan counties are not more likely than other households to experience food insecurity even when controlling for economic and sociodemographic variables.
Keywords: Food Security; Sociology; Sociology, General (0626)